2022
DOI: 10.1525/elementa.2021.00074
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and dynamic contributions to seasonal Arctic sea ice thickness distributions from airborne observations

Abstract: Sea ice thickness is a key parameter in the polar climate and ecosystem. Thermodynamic and dynamic processes alter the sea ice thickness. The Multidisciplinary drifting Observatory for the Study of Arctic Climate (MOSAiC) expedition provided a unique opportunity to study seasonal sea ice thickness changes of the same sea ice. We analyzed 11 large-scale (∼50 km) airborne electromagnetic sea thickness and surface roughness surveys from October 2019 to September 2020. Data from ice mass balance and position buoys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 90 publications
2
14
1
Order By: Relevance
“…It is also likely that, in autumn, basal growth contribution to ice production in pack ice is larger than from January to March, as level ice and its snow layer are generally thinner, hence allowing for more heat loss from the ocean in ice covered areas. von Albedyll et al (2022) suggest that the higher contribution of leads to ice production in spring than in winter could be partly resulting from regional differences, as the vessel drifted towards regions with a higher contribution of leads to the ice production. Our model suggests this is likely the case (Figure 11b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also likely that, in autumn, basal growth contribution to ice production in pack ice is larger than from January to March, as level ice and its snow layer are generally thinner, hence allowing for more heat loss from the ocean in ice covered areas. von Albedyll et al (2022) suggest that the higher contribution of leads to ice production in spring than in winter could be partly resulting from regional differences, as the vessel drifted towards regions with a higher contribution of leads to the ice production. Our model suggests this is likely the case (Figure 11b).…”
Section: Discussionmentioning
confidence: 99%
“…Fine-scale sea-ice dynamics also impact the sea ice mass balance. Divergent features in the ice, like leads and polynyas, are associated with localised intense ocean heat loss that enhances sea ice production in winter (Kwok, 2006;Wilchinsky et al, 2015;von Albedyll et al, 2022). The magnitude of ice production in leads remains largely uncertain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, our Eulerian deformation term can be considered Lagrangian dynamics. Two Lagrangian studies of dynamics observed along the MOSAiC drift track offer useful context for validating our Eulerian results (von Albedyll et al, 2022;Koo et al, 2021). The comparison is necessarily between our weekly Eulerian deformation term-i.e., Lagrangian dynamics-from closest in space and time to the MOSAiC drift track and dynamics as described within those studies.…”
Section: Discussionmentioning
confidence: 88%
“…The Multidisciplinary drifting Observatory for the Study of Arctic Climate (MOSAiC; Nicolaus et al, 2022) presented an opportunity for partitioning thermodynamic and dynamic growth from a Lagrangian perspective along the Transpolar Drift over a full year from October 2019 to September 2020. von Albedyll et al (2022) analyzed data from airborne electromagnetic (AEM) surveys and an ice mass balance buoy network to characterize the annual cycle of both dynamic and thermodynamic sea ice thickness contributions experienced by the ice pack surrounding the MOSAiC drift station. Thermodynamic growth was modeled using ice mass balance buoy temperature profiles and subtracted from overall ice growth captured by the airborne electromagnetic survey data in order to calculate dynamic sea ice effects as a residual.…”
Section: Introductionmentioning
confidence: 99%